2022
DOI: 10.3390/w14030283
|View full text |Cite
|
Sign up to set email alerts
|

The Stability Analysis of Tension-Leg Platforms under Marine Environmental Loads via Altering the Connection Angle of Tension Legs

Abstract: Tension-leg platforms have attracted increasing attention due to their smaller motion responses in platform planes among various offshore floating platforms. To better utilize wind energy sources, this paper carried out an improved modelling calculation for tension-leg floating foundations. A comparative study was conducted on the dynamic responses under environmental loading conditions via altering the tension legs’ connection angle. Based on potential flow theory and the Morison formulation, this paper estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Goupee et al [19] conducted 1:50 scale model experiments on the NREL 5 MW tension-leg floating wind turbine, which determined the free decay characteristics of the tension-leg platform and the dynamic response of the floating platform under different environmental loads, providing a large amount of experimental data for numerical analysis. Xu et al [20] conducted a dynamic response study on the connection angle of a tension leg floating platform under environmental load conditions. The results showed that the improved floating platform effectively reduced the dynamic surge and pitch responses, improving the stability of the tension leg platform.…”
Section: Introductionmentioning
confidence: 99%
“…Goupee et al [19] conducted 1:50 scale model experiments on the NREL 5 MW tension-leg floating wind turbine, which determined the free decay characteristics of the tension-leg platform and the dynamic response of the floating platform under different environmental loads, providing a large amount of experimental data for numerical analysis. Xu et al [20] conducted a dynamic response study on the connection angle of a tension leg floating platform under environmental load conditions. The results showed that the improved floating platform effectively reduced the dynamic surge and pitch responses, improving the stability of the tension leg platform.…”
Section: Introductionmentioning
confidence: 99%